Effects of neutrophil extracellular traps during human respiratory syncytial virus infection in vitro - Diniz, L. F.A. [UNESP]; Matsuba, B. K. [UNESP]; Souza, P. S.S. [UNESP]; Lopes, B. R.P. [UNESP]; Kubo, L. H. [UNESP]; Oliveira, J. [UNESP]; Toledo, K. A. [UNESP] (My University, 2021)
The human respiratory syncytial virus (hRSV) is the most common cause of severe lower respiratory tract diseases in young children worldwide, leading to a high number of hospitalizations and significant expenditures for health systems. Neutrophils are massively recruited to the lung tissue of patients with acute respiratory diseases. At the infection site, they release neutrophil extracellular traps (NETs) that can capture and/or inactivate different types of microorganisms, including viruses. Evidence has shown that the accumulation of NETs results in direct cytotoxic effects on endothelial and epithelial cells. Neutrophils stimulated by the hRSV-F protein generate NETs that are able to capture hRSV particles, thus reducing their transmission. However, the massive production of NETs obstructs the airways and increases disease severity. Therefore, further knowledge about the effects of NETs during hRSV infections is essential for the development of new specific and effective treatments. This study evaluated the effects of NETs on the previous or posterior contact with hRSV-infected Hep-2 cells. Hep-2 cells were infected with different hRSV multiplicity of infection (MOI 0.5 or 1.0), either before or after incubation with NETs (0.5-16 μg/mL). Infected and untreated cells showed decreased cellular viability and intense staining with trypan blue, which was accompanied by the formation of many large syncytia. Previous contact between NETs and cells did not result in a protective effect. Cells in monolayers showed a reduced number and area of syncytia, but cell death was similar in infected and non-treated cells. The addition of NETs to infected tissues maintained a similar virus-induced cell death rate and an increased syncytial area, indicating cytotoxic and deleterious damages. Our results corroborate previously reported findings that NETs contribute to the immunopathology developed by patients infected with hRSV.